Foreign ownership and openness in the Malaysian food processing industry: impact on productivity growth. - Yodfiatfinda,; Shamsudin, Mad Nasir; Mohamed, Zainalabidin; Yusop, Zulkornain; Radam, Alias (2011)
Food processing industry plays an important role in the Malaysian economy. The industry contributes about 10% to the total manufacturing output. This study aims to investigate the impacts of foreign ownership and openness to productivity growth in the Malaysian Food Processing Industry (FPI). A non parametric approach Data Envelopment Analysis (DEA) was employed to examine the total factor productivity growth. We employ five-digit panel data for the period of 2000-2006. The data was tested for stationary using Augmented Dickey Fuller (ADF) unit root test, and Hausman specification test to obtain the more appropriate model. Fixed effect model is the best model for estimation factor affecting total factor productivity growth in the small and medium enterprises (SMEs) and the large scale enterprises (LSEs). The Malaysian FPI was experiencing with negative total factor productivity growth (- 1.3%) in the SMEs and positive (7.3%) in the LSEs during 2001 to 2006. The results also suggest that foreign ownership is positively affecting total factor productivity growth both in the SMEs and the LSEs but not significant. However, openness is positively influencing the productivity growth in the SMEs and significant at five percent confidence level in the LSEs.